Legal problems of organization of state environmental control over the rational use of mineral resources in Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The problem of legal regulation of the institute of state ecological control over the rational use of mineral resources in Kazakhstan is regarded in this article. National legislation in the sphere of protection and use of mineral resources is analyzed in this study. Characteristics of a regulations governing state environmental control are allocated and described herein. The recommendations for making adjustments to the legislation, aimed at optimizing the organization of state environmental control which are based on the analysis are given by the author.Key words: subsoil, protection of mineral resources, subsurface management, green economics, environmental control and monitoring, codification of mining law, rational use of mineral resources.The problem of legal regulation of the institute of state ecological control over the rational use of mineral resources in Kazakhstan is regarded in this article. National legislation in the sphere of protection and use of mineral resources is analyzed in this study. Characteristics of a regulations governing state environmental control are allocated and described herein. The recommendations for making adjustments to the legislation, aimed at optimizing the organization of state environmental control which are based on the analysis are given by the author.Key words: subsoil, protection of mineral resources, subsurface management, green economics, environmental control and monitoring, codification of mining law, rational use of mineral resources.